Human dietary intake and hazard characterization for residues of neonicotinoides and organophosphorus pesticides in Egyptian honey. Issue 9 (26th November 2017) - Al Naggar, Yahya; Codling, Garry; Giesy, John P.
ABSTRACT: In two recently published reports, hazards posed by dietary exposure to organophosphate and neonicotinoid plant protection products on the European honey bee ( Apis mellifera L.) in Egypt were investigated. Using concentrations reported in those studies, an assessment of hazards posed by these two classes of insecticides to humans due to consumption of Egyptian honey from the Nile Delta during both spring and summer was performed. Twenty-eight compounds including metabolites were assessed for exposure of adult Egyptians based on the best- and worst-case scenarios. Even for the worst-case scenario, exposure to these two classes of pesticides in honey was 15-fold less than hazard index value of 1.0 for adverse effects on humans. Based upon this analysis, people exposed to these insecticides through consumption of honey products would be unlikely to exhibit adverse health outcomes.